Location of areas of emission of pollutants when poor urban air quality is detected. (23rd June 2021) - Mellado, Daniela; Gutierrez, María A.; Lerner, Jorge E. Colman; Demetrio, Pablo M.; Porta, Andrés A.; Jacovkis, Pablo M.; Sanchez, Erica Y.
Air pollution constitutes an environmental risk, evidenced in large urban centres. This work applies a methodology capable of detecting the areas of emission of pollutants when episodes of poor urban air quality are observed. This is carried out coupling air quality indices proposed by United States Environmental Protection Agency with the receptor model known as Nonparametric Trajectory Analysis. As a control case, observed concentrations (2013-2015) in Bahia Blanca (Argentina) were analysed, highlighting particulate matter as a dominant pollutant for episodes of poor air quality. Likewise, the application of the methodology allowed to reduce the number of possible stationary emission sources by 75%, and to highlight the implication of nearby linear sources. The strength of the methodology lies in visualising in real time, or in diagnostic mode, the potential areas of emission and their significance.